Leukaemia cutis after starting bendamustine: cause or coincidence?. (21st September 2015) - Mawri, Sagger; Nabi, Shahzaib; Jallad, Bassel; Won, Joseph
Abstract : A 55-year-old man with a history of chronic lymphocytic leukaemia presented with diffuse skin lesions that began 1 week after starting a new chemotherapy regimen with bendamustine and rituximab. The lesions appeared as erythematous papules that were neither itchy nor tender, and did not blanch with pressure. Initially, they began on his scalp and flanks and, over the next few days, spread diffusely throughout his body, becoming darker in colour. Skin biopsy showed atypical clonal B-cell proliferation in a perivascular, periadnexal and dermal band-like distribution, which was further characterised by immunohistochemical evaluation. These findings were suggestive of leukaemia cutis and consistent with the patient's chronic lymphocytic leukaemia, which was previously confirmed by bone marrow biopsy. The bendamustine was stopped and the patient's chemotherapy regimen was switched to fludarabine, cyclophosphamide and rituximab. Shortly thereafter, the leukaemia cutis regressed significantly.